Mutation of lysine-specific demethylase 5 is associated with enhanced tumor immunity and favorable outcomes in pan-cancer immune checkpoint blockade - Xiaofeng Li; Zhishan Zhang; Yingying Li; Lijin Chen; Yan Huang; Lijuan Su; Wenjun Xu; Yanni Hong; Jianjiao Li; Mujin Chen; Hongkui Yang; Hong Zhao; et al. (Molecular Cancer)
Abstract The lysine-specific demethylase 5 (KDM5) family, a key post-translational modification of chromatin, can shape tumor immune microenvironment. Here, we performed an extensive clinical and bioinformatic analysis to explore the association between KDM5 mutation and tumor immunity and its impact on the outcomes in pan-cancer immunotherapy. In 2943 patients across 12 tumor types treated with immune checkpoint inhibitors, KDM5-mutant tumors were associated with favorable overall survival (hazard ratio, 0.72; 95% confidence interval, 0.59–0.87; P = 0.004) and objective response rate (41.7% vs. 26.8%; P = 0.001). Further multi-omics analysis revealed KDM5 mutation was related to boosted tumor immunogenicity, enriched infiltration of immune cells, and improved immune responses. In summary, KDM5 mutation indicates enhanced tumor immunity and favorable outcomes in pan-cancer immune checkpoint blockade. These results have implication for treatment decision-making and developing immunotherapy for personalized care.